Who actually decides? Parental influence on the housing tenure choice of their children. (February 2018) - Lux, Martin; Samec, Tomáš; Bartos, Vojtech; Sunega, Petr; Palguta, Jan; Boumová, Irena; Kážmér, Ladislav
We focus on the role of within-family socialisation and the relationship between socialisation and resource transfers in the intergenerational transmission of housing preferences, the formation of familial housing attitudes and thus the reproduction of a normative housing tenure ladder across generations in Czech society. We show that resource transfers and the within-family socialisation of housing preferences, including preferences concerning housing tenure, are closely interconnected. In other words, parental influence on decision to buy own housing (and on housing preferences in general) of their adult children through socialisation is stronger if there is an (actual or assumed) intergenerational resource transfer. This has several implications for how housing markets and systems work. The paper draws on findings from qualitative, quantitative and experimental studies.